Effect of Nutrient Management on Yield of Bt Cotton under Dry Farming Conditions in North Saurashtra Agro-climatic Zone - Vora, V D; Hirpara, D S; Vekariya, P D; Vala, F G; Modhvadiya, V L (Annals of Arid Zone, 2019)
.Â